2022
DOI: 10.1038/s41598-022-10932-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and treatment of elderly onset adult-onset Still’s disease

Abstract: Adult-onset Still’s disease (AOSD)—a systemic inflammatory disease—often occurs at a young age. Recently, elderly onset patient proportion has been increasing; however, data are limited. To evaluate the characteristics of elderly patients with AOSD in a multicenter cohort, we retrospectively analyzed 62 patients with AOSD at five hospitals during April 2008–December 2020. Patients were divided into two groups according to age at disease onset: younger-onset (≤ 64 years) and elderly onset (≥ 65 years). Clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
(42 reference statements)
2
8
1
Order By: Relevance
“…An increased rate of mortality in elderly onset AOSD patients was observed in previous studies [23,24], and Suda et al also reported the more frequent presence of DIC in AOSD patients over 70 years old [42]. Moreover, although the pleuritis was not related to death in previous studies, Maruyama et al and Kishida et al showed an increased frequency of pleuritis in the elderly onset AOSD patients [22,23]. Thus, the elderly onset AOSD patients may characterized with worse prognosis including higher mortality and higher frequency of complications.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…An increased rate of mortality in elderly onset AOSD patients was observed in previous studies [23,24], and Suda et al also reported the more frequent presence of DIC in AOSD patients over 70 years old [42]. Moreover, although the pleuritis was not related to death in previous studies, Maruyama et al and Kishida et al showed an increased frequency of pleuritis in the elderly onset AOSD patients [22,23]. Thus, the elderly onset AOSD patients may characterized with worse prognosis including higher mortality and higher frequency of complications.…”
Section: Discussionmentioning
confidence: 81%
“…The outcome and treatment were not signi cantly different in two groups, however, AOSD patients with MAS had an increased prevalence of relapse. To our knowledge, our research is one of the largest studies to investigate the different clinical features and outcome of elderly onset AOSD patients [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 49–51 Further work has been done to highlight the clinical heterogeneity of AOSD, with a study showing they may fall into four distinct phenotypes, each characterised by a single prominent clinical feature (high CRP, high ferritin, high systemic score, low CRP/ferritin), raising the possibility of risk stratification and targeted therapies in future. 52 …”
Section: Adult Onset Still’s Diseasementioning
confidence: 99%
“…[49][50][51] Further work has been done to highlight the clinical heterogeneity of AOSD, with a study showing they may fall into four distinct phenotypes, each characterised by a single prominent clinical feature (high CRP, high ferritin, high systemic score, low CRP/ferritin), raising the possibility of risk stratification and targeted therapies in future. 52 When comparing presentation by age, those that develop AOSD aged 65 or above similarly present with fever, arthralgia, and skin rashes, though are less likely to develop pharyngitis and more likely to develop pleuritis. 53,54 Those with an elderly onset are 3-5-times more likely to develop life-threatening complications such as disseminated intravascular coagulopathy (DIC) and MAS, highlighting the need for prompt recognition and management in this population.…”
Section: Adult Onset Still's Diseasementioning
confidence: 99%